Dermoscopy of a rare case of linear syringocystadenoma papilliferum with review of the literature - Payal Chauhan (Mattioli1885, 2018)
Syringocystadenoma papilliferum (SCAP) is a benign hamartomatous tumor arising from pluripotent cells with either apocrine or eccrine differentiation. We report a rare case of de novo linear SCAP in a 12-year-old female child with lesions over the chest along with the dermoscopic findings.